A description of virtual skills workshops for supporters of loved ones with eating disorders: Indicators of benefit and acceptability, clinical reflections and consideration of neurodiversity. (21st July 2022) - Harrison, Amy; Folk, Rebecca; Proud, Faye; Webb, Jessica; Oyeleye, Oyenike; Clark Bryan, Danielle; Webb, Joyce; Webb, Hannah; Whitaker, Wendy; Dhopatkar, Namrata; Treasure, Janet
Abstract: Objective: Providing information and support to those supporting a loved one with an eating disorder is a key part of evidence‐based service provision. We report on how we took our workshops for supporters online during the Covid‐19 Pandemic when country‐side physical distancing restrictions meant we were unable to work face to face. Methods: We outline the structure of an eight‐session 2‐h workshop series delivered fortnightly facilitated by a multidisciplinary team of clinicians, researchers and experts by experience. We use a repeated‐measures design to understand the possible benefits of the workshops on supporter skills ( n = 76). Results: Measured using the Caregiver Skills Scale, we observed small‐sized improvements in the overall skills ( D = 0.43) of n = 17 supporters who provided data at the end of the intervention. Supporters gave largely positive feedback on the virtual format. They particularly liked the opportunity to interact with other supporters. As facilitators, we overcome our initial anxiety around workshop delivery using a new platform and reflected that having more time to cover key information and for skills practice over a period of 16 weeks offered opportunities to develop and reflect on new skill together as a group. We were also able to work with larger groups of supporters, as several barriers to access were removed. Conclusions: As the workshops reached a larger number of supporters than through face to face delivery and were of benefit to those who reported on their skills, we plan to continue offering workshops to supporters online in future. Key points: The National Institute for Health and Care Excellence (NICE) Guidelines for eating disorders recommend that those supporting loved ones with eating disorders have access to information and support. Online workshops for supporters might remove barriers to access and increase uptake, and we wanted to learn more about this mode of delivery and its benefits on supporter skills. We were also interested in thinking about neurodiversity within the workshops, in particular whether supporters have traits of autism spectrum disorder. This information is important in helping us plan for more inclusive workshops. Around 1/3 of supporters scored over the cut‐off on the Autism Quotient (AQ10) suggesting it is important to think carefully about how online workshops might benefit (or present challenges for) a more diverse group of attendees. Supporters reported benefits in terms of improvements in their skills and positive feedback at the end of one of five workshop series.